2011
DOI: 10.1158/1078-0432.ccr-11-1074
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Safety and Pharmacokinetic Study of Bavituximab, a Chimeric Phosphatidylserine-Targeting Monoclonal Antibody, in Patients with Advanced Solid Tumors

Abstract: Purpose: Bavituximab is a chimeric immunoglobulin G1 phosphatidylserine-targeting monoclonal antibody that triggers vascular disruption and enhances antitumor immune response. This phase I study assessed the safety and pharmacokinetics of bavituximab in patients with advanced solid tumors.Experimental Design: Patients with refractory advanced solid tumors were enrolled into four sequential dose-escalation cohorts (0.1, 0.3, 1, or 3 mg/kg bavituximab weekly) with two dosing schedules. Patients in the 0.1 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…2aG4, a mouse immunoglobulin G2a (IgG2a) version of the human chimeric antibody bavituximab, localizes to phosphatidylserine-expressing tumor vascular endothelium and elicits strong antitumor effects when combined with chemo-or radiotherapy in mouse tumor models (24,27,28). Bavituximab is currently being tested in multiple clinical trials (38)(39)(40). Despite the progress that has been made, the mechanism of action of anti-phosphatidylserine antibodies is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2aG4, a mouse immunoglobulin G2a (IgG2a) version of the human chimeric antibody bavituximab, localizes to phosphatidylserine-expressing tumor vascular endothelium and elicits strong antitumor effects when combined with chemo-or radiotherapy in mouse tumor models (24,27,28). Bavituximab is currently being tested in multiple clinical trials (38)(39)(40). Despite the progress that has been made, the mechanism of action of anti-phosphatidylserine antibodies is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Bavituximab, the human chimeric version of 2aG4, in combination with chemotherapy, is being used to treat patients with cancer in randomized clinical trials (38)(39)(40). Impressive antitumor effects in patients with cancer have been obtained with other antibodies that enhance tumor immunity, including anti-PD1, anti-PD-1L, and ipilimumab (anti-CTLA-4; ref.…”
mentioning
confidence: 99%
“…In summary, we have shown that PS-targeting antibodies improve the efficacy of anti-CTLA-4 or anti-PD-1 therapy in murine models of melanoma, suggesting that these combinations have the potential to improve outcome in patients with advanced-stage melanoma. Bavituximab, a chimeric PS-targeting antibody, is currently being evaluated in late-stage clinical trials for the treatment of cancer patients with solid tumors (46,54), and strong antitumor activity has been demonstrated in melanoma clinical trials using checkpoint inhibitor antibodies targeting CTLA-4 (10), PD-1 (12,13), and PD-L1 (55). It is increasingly apparent that successful immunotherapy requires tumor cell killing, induction of proinflammatory immune responses, and concomitant reduction of immunosuppressive signals leading to increased tumor infiltration by activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that PS-targeting antibodies localize to PS-expressing tumors and tumor endothelial cells and elicit strong antitumor effects when combined with chemotherapy or radiotherapy (33,41,42,44). A PS-targeting antibody, bavituximab, is currently being tested in multiple advanced stage clinical trials for the treatment of solid tumors (45,46).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of this therapy is based on the exposure of phosphatidylserine on the external leaflet of the plasma membrane, a preapoptotic event in cells infected by a broad variety of viruses. The safety and pharmacokinetics of this antibody have been already evaluated in clinical trials for treatment of other human disorders [201]. Another example of the use of antiphospholipidantibodies to combat a viral disease is provided by HIV, since different antiphospholipid antibodies have shown a broad neutralizing activity against this virus [161].…”
Section: Phosphlipids As Antiviral Targetsmentioning
confidence: 99%